Estimating private provision of public goods with heterogenous participants: A structural analysis - Yonghong An; Yingyao Hu; Pengfei Liu (Centre for Microdata Methods and Practice (cemmap), 2015)
This paper estimates a structural model of private provision of public goods to provide some new empirical evidence on individuals' strategic contributing behaviors. In the model, individuals' contributing behaviors are allowed to be heterogenous and time-varying. We show that all the main components of the model including the number of different contributing strategies, functional form for each strategy, and how individuals adjust their strategies are identified from the revealed contribution choices of individuals. Further, the structural model is estimated using the data collected in a threshold public good experiment. The empirical results suggest that subjects in our experiment employ three contributing strategies, and they strategically respond to provision history by adjusting their preceding behavior. In addition, the response is heterogenous and dependent on subjects' contributing strategies.
Keywords: H41; C14; 330; Public Goods; Private Provision; Measurement Errors; Unobserved Heterogeneity; Nonparametric Identification and Estimation; Experimental Data